Parasitism :the diversity and ecology of animal parasites - Goater, Timothy M. (CUP, 2014)
"Reflecting the enormous advances made in the field over the past ten years, this text synthesizes the latest developments in the ecology and evolution of animal parasites against a backdrop of parallel advances in parasite systematics, biodiversity and life cycles. This second edition has been thoroughly revised to meet the needs of a new generation of parasitology students. Balancing traditional approaches in parasitology with modern studies in parasite ecology and evolution, the authors present basic ecological principles as a unifying framework to help students understand the complex phenomenon of parasitism. Richly illustrated with over 250 figures, the text is accompanied by case study boxes designed to help students appreciate the complexity and diversity of parasites and the scientists who study them. This unique approach, presented clearly and with a minimum of jargon and mathematical detail, encourages students from diverse backgrounds to think generally and conceptually about parasites and parasitism"--